PERFORMANCE OF ZAKAT INSTITUTIONS: MODIFICATION OF THE IZN (SURVEY AT NATIONAL BOARD OF ZAKAT AND LAZIS IN KEBUMEN REGENCY) - Siti Maryam; Hilda Monoarfa; Firmansyah Firmansyah (STIESA Press, 2021)
Nowadays, the growth of the Zakat Management Organization (OPZ) in Indonesia can be said as a positive indication. However, the utilization of collected ZIS funds has not been optimal and is still far from its potential. This is related to the performance of zakat institutions which are supported by all elements; a society in the aggregation and its institution. That is why the measuring instrument is needed to make the performance of zakat can be more optimal. This study aims to analyze the performance of zakat institutions in Kebumen District in purpose describe perform of the zakat institution. This study used primary data from interviewing the leaders and questionnaires with 200 respondents at BAZNAS and LAZISMU, Kebumen district. The three variables used in this study are a database of institutions, institutional, and impact of zakat on the community of mustahik. The method is a method slot deposit 5000 of measuring performance by using a modified measurement of the National Zakat Index (IZN). The results of this study indicated that BAZNAS in Kebumen district has a performance index value in the good category, and LAZISMU in Kebumen district has a good performance index value. These results is affected by the differential of institutional variable values between BAZNAS and LAZISMU.